The Practical Approach of Cultural Communication between China-ASEAN in the Era of Digital Intelligence - Tang, Rongshuang (JOURNAL OF ADVANCES IN LINGUISTICS, 2025)
In the era of digital intelligence, China-ASEAN cultural exchanges demonstrate significant potential in fostering intercultural exchange, shaping a positive national image, and preserving global cultural diversity. Facing this opportunity, it is crucial to leverage the technological advantages of digitization to empower users, platforms, and algorithms, while deeply integrating into the entire process of cultural interaction, dialogue environments, and the functionality of cultural communication entities. To achieve effective cultural transmission, it is not only essential to rely on technological advancements but, more importantly, to foster discursive synergy and mutual benefit. Therefore, enhancing the interactivity of cultural communication, improving the dialogue environment, and strengthening the functional role of communication entities are fundamental strategies for advancing China-ASEAN cultural dissemination in the digital intelligence era. These efforts also serve as vivid examples of China-ASEAN cooperation in building a community with a shared future for mankind.